Product Design of Card Game with the Theme of Mental Health for Teenagers - Gunawan, Livia Angelica (Universitas Ciputra, 2021)
This research contains the product development of the card game, Wellbeing, which is a game published under Petualangan Menuju Sesuatu that attempts to simulate different events and coping mechanisms as a means to educate players about mental health management. The methods used in this research are qualitative and quantitative research through interviews with expert and extreme users, as well as surveys to the target consumer and literature studies. The purpose of this research is to discover whether or not the card game, Wellbeing, is already able to answer the needs of its target market. The results afterwards show that the game is already able to garner positive response from the public as well as provide them with content that can give appropriate educational value and thereby solve the problem which is the lack of coherence between the initial iteration of the product and its target market at the time. Keywords: board game, educational game, mental health literacy, gameplay mechanic, target market fit